Factors Causing Pending Claims on Health BPJS Patients with Fishbone Diagrams at Al–Hikmah Clinic Sukorejo Ponorogo Districrt - Hindun Al Istiqomah; Dwi Nurjayanti (Jurnal Rekam Medis dan Informasi Kesehatan Indonesia, 2025)
Pending BPJS Health claims are claim returns where there is no agreement between BPJS Health and FKRTL regarding coding or medical principles (claim disputes), but resolution is carried out in accordance with BPJS Law Number 7 of 2018. The purpose of this research is to identify the factors causing pending claims using the Fishbone diagram approach, which includes the aspects of Man, Money, Method, Machine, and Material. The type of this research is a qualitative descriptive method using interviews and observations. The population of this study consists of all inpatient and outpatient insurance officers at Al-Hikmah Clinic. The sampling techniques used are total sampling and purposive sampling. Data were analyzed descriptively. Based on the research results at Al-Hikmah Sukorejo Clinic, the factors causing pending claims include the absence of staff with a background in medical records, incomplete claim documents, system errors in the P-Care application, and internet network issues. Continuous training, improvement of the digital system, and adjustment of SOPs are needed to minimize pending claim cases and enhance service efficiency. The researchers' recommendation is to always check the completeness of claim documents for the BPJS insurance claim process and to conduct regular training for claim officers at the clinic.